Successful Medical Treatment of Adult Nesidioblastosis With Pasireotide over 3 Years: A Case Report. Issue 14 (April 2016) - Schwetz, Verena; Horvath, Karl; Kump, Patrizia; Lackner, Carolin; Perren, Aurel; Forrer, Flavio; Pieber, Thomas R.; Treiber, Gerlies; Sourij, Harald; Mader, Julia K.
Abstract : Abstract: Nesidioblastosis is a rare cause of endogenous hyperinsulinemic hypoglycemia in adults. Diagnosis is often challenging and therapeutic options are scarce. In 2009, a 46-year-old female patient presented with recurrent severe hypoglycemia and immediate recovery after glucose ingestion. Although 72-h-fasting test was positive, various imaging technologies (sonography, computed tomography, somatostatin receptor scintigraphy, dopamine receptor positron emission tomography [DOPA-PET]) were negative. Endoscopic ultrasound revealed a lesion in the pancreatic corpus, whereas selective arterial calcium stimulation test, portal venous sampling and GLP-1-receptor scintigraphy were indicative of a lesion in the pancreatic tail, which was surgically removed. The histopathologic examination revealed beta cell hyperplasia and microadenomas expressing glucagon. After surgery, the patient was free of symptoms for 6 months, after which hypoglycemic episodes recurred. After unsuccessful treatment with corticosteroids and somatostatin analogs, treatment with pasireotide, a novel somatostatin analog with high affinity to somatostatin receptor 5 and a possible side effect of hyperglycemia, was initiated (0.6 mg BID). To date, our patient has been free of severe hypoglycemic episodes ever since. Yearly repeated imaging procedures have shown no abnormities over the last 3 years. We report for the first time that pasireotide was successfully used in the treatment of adult nesidioblastosis.